STUDENTS' PERCEPTIONS OF THE APPLICATION OF ORIGAMI ART IN ENGINEERING DRAWING SUBJECT - Mohd Salehudin Marji; Nor Aisyah Che Derasid; Aede Hatib Musta'amal (Jurnal Scientia, 2023)
This study was conducted to examine the extent of the potential use of origami art in Engineering drawing subject. There are two objectives to be achieved in this study which are to evaluate the students' perception on the importance of origami art in education and also their perception on the application of origami art in engineering drawing learning. This study was conducted at Kolej Vokasional Tanjung Puteri Johor and involved a total of 30 students. A course implementing origami in engineering drawing subject was conducted and the research findings were obtained using survey forms distributed after the completion of the course. The results found that students had a positive perception towards the importance of origami art in education. In addition, for the second objective, students also gave a positive perception towards the application of origami art in engineering drawing learning.